A New Compression-Torsion-Tribometer with Scalable Contact Pressure for Characterization of Tool Wear during Plastic Deformation. (5th May 2015) - Teller, Marco; Seuren, Simon; Bambach, Markus; Hirt, Gerhard
Abstract : A contact pressure which reaches up to ten times the yield stress of the workpiece material is characteristic for cold extrusion processes. Common tests for friction and wear are limited to rather low contact pressures. Thus, the aim of this paper is to present a new compression-torsion-tribometer which is able to scale the contact pressure to a multiple of the yield stress of the workpiece. In order to enable a contact pressure that greatly exceeds the yield stress of the workpiece material, the workpiece specimen is encapsulated laterally. As main parameters, contact pressure, glide length, and relative velocity can be adjusted independently, thus allowing for multiple load cycles. The resulting torque is measured continuously as an indicator for wear. Afterwards wear can be also quantified by examination of surfaces. Hence, the developed setup enables a comparison of tool surfaces and coatings and a characterization of wear behaviour under high contact pressure.